Preparation process of high-sealing multi-layer waterproof adhesive label
Patent Information
- Application Number
- CN202611216165.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-27
Smart Images

Figure CN122991010A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of label sticker technology, and more specifically, it relates to a manufacturing process for a high-sealing, multi-layer waterproof self-adhesive label. Background Technology
[0002] Self-adhesive labels are composite materials made of paper, film, or other special materials as the face stock, coated with adhesive on the back, and backed with kraft paper or other materials that isolate the adhesive. Compared with traditional labels, self-adhesive labels have advantages such as not needing to apply glue, paste, or water, being pollution-free, and saving labeling time.
[0003] The preparation of self-adhesive labels requires first applying adhesive to the fabric paper, then cutting the fabric paper, and finally pasting the cut fabric paper onto the base paper. Currently, the following problems exist in the preparation of self-adhesive labels: 1. Existing multi-layer waterproof self-adhesive labels are prone to interlayer water seepage and capillary seepage at the cut surface, leading to blistering, delamination, and insufficient waterproof durability under long-term humid or immersion environments; 2. Existing processes cannot simultaneously block these two water vapor penetration paths; ordinary composite adhesives have insufficient water resistance, easily absorbing water and swelling after immersion, making it difficult to maintain a stable interlayer seal over a long period, ultimately resulting in a short service life for the label's waterproof seal. Summary of the Invention
[0004] To address the aforementioned issues, this application provides a process for manufacturing high-sealing, multi-layer waterproof self-adhesive labels.
[0005] In a first aspect, this application provides a manufacturing process for highly sealing, multi-layer waterproof self-adhesive labels, employing the following technical solution: A manufacturing process for highly sealing, multi-layer waterproof self-adhesive labels includes the following steps: S1. Plasma activation pretreatment of the surface of the waterproof substrate; S2. A cross-linked sealing prepolymer is continuously coated on one side of the activated surface waterproof substrate to form a pre-sealing coating. S3. The surface waterproof substrate with pre-sealed coating is combined with the water-blocking barrier membrane in a segmented gradient hot-pressing process, so that the pre-sealed coating undergoes an in-situ cross-linking reaction at the interface of the two substrates to generate a continuous sealing transition layer, thus obtaining a double-layer composite membrane. S4. Apply a modified waterproof adhesive layer to the side of the water-blocking membrane that is away from the sealing transition layer. S5. A release film is laminated onto the surface of the self-adhesive layer to produce a multi-layer waterproof self-adhesive roll material. S6. The roll material is die-cut to obtain the label blank. Then, UV sealant is applied online to the die-cut surface of the label blank. After UV curing, the cross-section is sealed to obtain a high-sealing multi-layer waterproof self-adhesive label.
[0006] By employing the above technical solution, plasma activation pretreatment is used to enhance the surface activity of the waterproof substrate, thereby strengthening the interfacial bonding between the pre-sealed coating and the substrate. Subsequently, a cross-linked sealing prepolymer is applied and composited through segmented gradient hot pressing, promoting in-situ cross-linking of the pre-sealed coating at the interface between the waterproof substrate and the water-blocking membrane. This forms a continuous sealing transition layer, sealing the microscopic gaps at the interface between the two membrane layers and preventing water vapor from penetrating along the interlayer interface. Waterproof self-adhesive coating and release film lamination are then sequentially completed to obtain a roll material. After die-cutting, UV sealant is applied to the exposed die-cut surface and cured under UV light to achieve cross-sectional sealing, preventing water vapor from capillary penetration through the die-cut surface. By successively constructing an interlayer interface sealing structure and a die-cut surface sealing structure, a dual waterproof barrier system is formed, simultaneously blocking two main water vapor penetration channels. This effectively alleviates the problems of interlayer seepage, bubbling, and delamination in labels under high humidity and immersion environments, significantly improving the overall sealing performance and waterproof durability of multi-layer self-adhesive labels.
[0007] Preferably, in step S1, the surface waterproof substrate is any one of PET waterproof film, BOPP film, or hydrophobic modified PE film, and the plasma activation adopts atmospheric pressure plasma treatment with a treatment power of 80-160W, a treatment distance of 4-10mm, and a treatment speed of 10-30m / min.
[0008] Preferably, in step S2, the crosslinked sealing prepolymer is a hydrophobically modified isocyanate-terminated polyurethane prepolymer, which is prepared by the following parts by weight of raw materials: 65-85 parts of hydrophobic polycarbonate diol, 10-30 parts of isophorone diisocyanate, 1-5 parts of long-chain alkyl hydrophobically modified monomer, 0.01-0.15 parts of dibutyltin dilaurate, and 0.2-1 parts of dehydrating agent.
[0009] Preferably, in step S3, the method for preparing the crosslinked sealing prepolymer includes: vacuum dehydrating hydrophobic polycarbonate diol; sequentially adding isophorone diisocyanate and long-chain alkyl hydrophobic modified monomers under nitrogen protection, adding dibutyltin dilaurate, and then carrying out an addition reaction at 75-85°C; cooling down after the free NCO content reaches 2.0%-3.2%, adding a dehydrating agent, mixing, filtering, and encapsulating to obtain the crosslinked sealing prepolymer.
[0010] Preferably, in step S3, the thickness of the coated dry film is controlled between 2 and 12 μm; the segmented gradient hot pressing is divided into two stages: the first stage is low-pressure exhaust, with a hot pressing temperature of 45 to 55°C and a roller pressing pressure of 0.2 to 0.6 MPa; the second stage is high-pressure cross-linking and lamination, with a hot pressing temperature of 55 to 75°C and a roller pressing pressure of 0.8 to 1.6 MPa; the lamination linear speed is 5 to 25 m / min.
[0011] Preferably, during the segmented gradient hot-pressing composite process in step S3, the relative humidity of the production environment is controlled at 30% to 60%; the interface temperature between the surface waterproof substrate and the water-blocking barrier film is maintained at 40 to 70°C, so that the pre-sealed coating can undergo a stable in-situ cross-linking reaction and avoid the formation of bubble defects at the interface.
[0012] Preferably, in step S4, the water-blocking barrier film is one of aluminum-plastic composite film, PVDC coated film or EVOH barrier film, and the modified waterproof self-adhesive is acrylate hydrophobic modified pressure-sensitive adhesive with a dry film thickness of 15-45 μm and hydrophobic nano silica particles dispersed in the adhesive layer.
[0013] Preferably, in step S5, the release film is a single-sided silicone-coated PET release film with a thickness of 38-50 μm; the release film is placed on the outside of the modified waterproof self-adhesive layer to isolate and protect the self-adhesive layer and prevent the self-adhesive from self-adhesion and contamination during roll storage and die-cutting processes; when the label is pasted and used, the release film is peeled off.
[0014] Preferably, in step S6, the UV sealant is a UV acrylic resin system containing hydrophobic monomers, the coating width covers the cut surface of the mold, the UV sealant coating thickness is 2-8 μm, and the UV curing exposure dose is 600-1200 mJ / cm².
[0015] Preferably, the high-sealing multilayer waterproof self-adhesive label comprises, from the outside to the inside: a surface waterproof substrate, a cross-linked sealing transition layer, a water-blocking barrier film, a modified waterproof self-adhesive layer, and a release film; the cross-linked sealing transition layer continuously fills the microscopic gaps between the surface waterproof substrate and the water-blocking barrier film.
[0016] In summary, this application has the following beneficial effects: 1. This application utilizes a cross-linked sealing prepolymer to form a continuous sealing transition layer at the interface of two film materials in situ. This layer can fill the microscopic gaps at the film material bonding interface and effectively inhibit water vapor from penetrating inward along the interlayer gaps. At the same time, UV sealing and curing treatment is applied to the die-cut cross-section to block the cut channels and prevent water vapor from capillary penetration. This achieves the synergistic effect of the dual sealing structure and significantly improves the sealing and waterproofing capabilities of the label in immersion and high humidity environments, delaying label bubbling and delamination failure.
[0017] 2. This application improves the surface inertness of the substrate by setting up a plasma activation pretreatment process for the surface waterproof substrate, enhances the adhesion of the pre-sealing coating to the substrate surface, prevents interface peeling of the sealing transition layer, and ensures the long-term stability of the interlayer sealing structure.
[0018] 3. This application adopts a segmented gradient hot-pressing composite process, first using low pressure to fully expel interfacial air, and then using high pressure to promote the cross-linking reaction, reducing air bubble defects in the sealing transition layer, ensuring the continuity and integrity of the sealing layer formed by cross-linking, and further ensuring the interlayer barrier effect. Attached Figure Description
[0019] Figure 1 This is a flowchart of a high-sealing, multi-layer waterproof self-adhesive label manufacturing process provided in this application; Figure 2 This is a comparison chart of the performance effects of this application. Detailed Implementation
[0020] The present application will be further described in detail below with reference to embodiments and comparative examples. Unless otherwise specified, the experimental methods used below are conventional methods. Unless otherwise specified, the materials, reagents, methods and instruments used are all conventional materials, reagents, methods and instruments in the art, which can be obtained by those skilled in the art through commercial channels or prepared according to literature methods.
[0021] Technical concept: Multi-layer self-adhesive labels are widely used in warehouse signage, outdoor product nameplates, and water-sensitive equipment markings. Existing multi-layer waterproof self-adhesive labels generally rely solely on a surface waterproof film for protection. However, the interfaces between the multiple film layers have micron-level gaps, and the edges are directly exposed after die-cutting. In immersion or high-humidity environments, moisture slowly diffuses and permeates along the micro-gaps between the film layers, and also undergoes capillary permeation through the die-cut surfaces, ultimately causing blistering, delamination, and peeling of the label layers, significantly shortening its lifespan. Conventional improvement methods mostly involve optimizing the adhesive layer alone or simply sealing the cut edges, which is insufficient to simultaneously block both moisture penetration channels. If ordinary composite adhesives are used, the adhesive layer easily absorbs water and swells upon contact with water, failing to maintain a dense, hydrophobic barrier interface in the long term, thus limiting the improvement in waterproof durability.
[0022] To address the aforementioned technical deficiencies, this application selects a hydrophobically modified isocyanate-terminated polyurethane prepolymer with specific components as the interlayer sealing material. Utilizing a segmented gradient hot-pressing process, the prepolymer undergoes an in-situ cross-linking reaction at the interface between the two membrane layers, forming a continuous and dense hydrophobic sealing transition layer that seals the microscopic gaps between the membrane materials. Furthermore, UV sealing is applied to the cut surface of the mold to block lateral moisture intrusion channels. Through the synergy of these two techniques, a three-dimensional double waterproof barrier is constructed, which is not a simple superposition of single protective measures but produces a synergistic waterproofing effect. The segmented gradient process of low-pressure venting followed by high-pressure cross-linking during hot pressing effectively avoids bubble defects at the cross-linking interface. Simultaneously, the prepolymer formulation requires precise control, as ordinary adhesives cannot form a stable hydrophobic cross-linking network.
[0023] The following are the main raw materials and reagents used in the examples and comparative examples, and their sources and specifications are as follows; unless otherwise specified, all reagents are commercially available analytical grade or higher products: 0. Toluenesulfonyl isocyanate can be used as a dehydrating agent; 2. Hydrophobic polycarbonate diols are selected from hydroxyl-terminated hydrophobic modified polycarbonate diols with a number average molecular weight of 1000-3000 g / mol. Aliphatic long alkyl chains are introduced into the main molecular chain to improve hydrophobic properties. Commercially available products such as Asahi Kasei T6002 and Wanhua PCD2000 can be used directly.
[0024] ·3. Long-chain alkyl hydrophobic modified monomers are C12-C18 alkyl modified monohydroxy acrylic acid / monohydroxy alkane monomers with a carbon chain length of 12-18 carbon atoms, such as dodecyl alcohol and octadecyl hydroxyethyl acrylate.
[0025] 4. The EVOH barrier film is an ethylene-vinyl alcohol copolymer, which is the raw material for the water-blocking barrier film used in this application; the PVDC coated film is polyvinylidene chloride, which can be used to prepare a high-barrier coated film as a candidate substrate for the water-blocking barrier film; the EVOH film is a commercially available film with an ethylene molar content of 24% to 38%; the PVDC coated film substrate is BOPP / PET, and the PVDC solid content of the coating layer is ≥40%; both conventional food-grade and packaging-grade water-blocking barrier films on the market can be selected.
[0026] 5. The UV acrylic resin (main body of UV sealant) is an aliphatic UV acrylic resin containing C8-C16 long alkyl hydrophobic side chains with a functionality of 2-4. Commercially available UV hydrophobic resins for die-cutting and sealing of self-adhesive materials (such as Sartoma and Changxing Chemical hydrophobic UV resin series) can be purchased and used directly.
[0027] 6. NCO represents isocyanate groups. Free NCO refers to the mass percentage of unreacted isocyanate groups remaining in the prepolymer, which is a key indicator for controlling the crosslinking activity of the prepolymer.
[0028] Preparation Example 1: The preparation process of the cross-linked sealing prepolymer is as follows: hydrophobic polycarbonate diol is added to the reactor and heated to 110℃ at a rate of 1.5℃ / min. The vacuum degree of the system is controlled to be ≤-0.090MPa, the stirring speed is 150r / min, and the system is dehydrated under constant temperature vacuum for 2.5h. After dehydration, nitrogen protection is applied for standby, and the moisture content of the material is controlled to be ≤0.05%. Under nitrogen protection, the reactor was stirred at 90 rpm. First, a measured amount of isophorone diisocyanate was added and stirred for 15 min. Then, the long-chain alkyl hydrophobic modified monomer was slowly added and stirred for 25 min until the system was homogeneous and transparent, completing the premixing of raw materials. After premixing, dibutyltin dilaurate was added and the mixture was heated to 80°C under sealed conditions for constant temperature reaction. The reaction was stirred continuously, and samples were taken every 1 hour to detect the free NCO value. When the measured free NCO value fell below 2.6%, the cooling system was turned on to lower the temperature to 55°C. A dehydrating agent was added and stirred for 35 min. The mixture was filtered through a 200-mesh filter to remove trace gel particles, and the filtrate was sealed and packaged under nitrogen protection.
[0029] Preparation Example 2: The UV sealant is an aliphatic UV acrylic resin system containing long-chain alkyl hydrophobic monomers. It can use commercially available hydrophobic UV sealing resins or be formulated in-house. A self-formulated formula is as follows: 50 parts aliphatic hexafunctional UV acrylic resin, 20 parts monofunctional long-chain hydrophobic acrylic monomers, 15 parts dipropylene glycol diacrylate reactive diluent, 4 parts 184 photoinitiator, 0.8 parts leveling agent, and 0.4 parts defoamer. The monofunctional long-chain hydrophobic acrylic monomers are C12-C18 alkyl acrylates, with hydrophobic side chains introduced to form a low surface energy hydrophobic film after curing, preventing water vapor capillary penetration. The 184 photoinitiator is suitable for medium- and high-pressure mercury lamp UV curing, matching a curing light intensity of 800 mJ / cm². The leveling agent and defoamer are general-purpose acrylic ester additives, eliminating coating pinholes and bubbles. This UV sealant only acts to seal the side of the die-cut surface and is an auxiliary structure of this application. It is not a core innovative material for achieving long-term waterproofing between layers. Commercially available hydrophobic UV edge-sealing adhesives for die-cutting can be directly replaced.
[0030] Example 1: This application provides a process for manufacturing high-sealing, multi-layer waterproof self-adhesive labels. The process includes the following steps: S1. Plasma activation pretreatment of the surface of the waterproof substrate; The surface waterproof substrate is any one of PET waterproof membrane, BOPP film or hydrophobic modified PE film. The plasma activation adopts normal pressure plasma treatment, with a treatment power of 120W, a treatment distance of 7mm and a treatment speed of 20m / min. S2. A cross-linked sealing prepolymer is continuously coated on one side of the activated surface waterproof substrate to form a pre-sealing coating. The crosslinked sealing prepolymer is a hydrophobically modified isocyanate-terminated polyurethane prepolymer, which is prepared from the following raw materials in parts by weight: 75 parts hydrophobic polycarbonate diol, 20 parts isophorone diisocyanate, 3 parts long-chain alkyl hydrophobically modified monomer, 0.08 parts dibutyltin dilaurate, and 0.6 parts dehydrating agent. Furthermore, the crosslinking sealing prepolymer is a solvent-free, single-component polyurethane coating liquid with a 100% solid content, requiring no additional organic solvents. For high-speed thin-coating applications, a small amount of anhydrous ethyl acetate can be added as a diluent, with the solid content of the coating liquid controlled at 80% after dilution. The dry film thickness is controlled to 7μm by adjusting the solid content of the coating liquid, the coating speed, and the coating roller gap: a high solid content of 95% is suitable for a thick coating of 9μm; a low solid content dilution system of 80% is suitable for a thin coating of 6μm. The solvent used for dilution is anhydrous ethyl acetate, which completely evaporates during the first stage of segmented hot pressing at 50℃ low pressure after coating, leaving no solvent residue and not affecting the subsequent in-situ crosslinking reaction at the interface. S3. The surface waterproof substrate with pre-sealed coating is combined with the water-blocking barrier membrane in a segmented gradient hot-pressing process, so that the pre-sealed coating undergoes an in-situ cross-linking reaction at the interface of the two substrates to generate a continuous sealing transition layer, thus obtaining a double-layer composite membrane. The method for preparing the cross-linked sealing prepolymer includes: vacuum dehydrating hydrophobic polycarbonate diol; sequentially adding isophorone diisocyanate and long-chain alkyl hydrophobic modified monomers under nitrogen protection, adding dibutyltin dilaurate and then carrying out an addition reaction at 80°C; cooling down after the free NCO content reaches 2.6%, adding a dehydrating agent and mixing, filtering and encapsulating to obtain the cross-linked sealing prepolymer; The coating dry film thickness is controlled at 7μm; the segmented gradient hot pressing is divided into two stages: the first stage is low-pressure exhaust, hot pressing temperature is 50℃, and roller pressing pressure is 0.4MPa; the second stage is high-pressure cross-linking and lamination, hot pressing temperature is 65℃, and roller pressing pressure is 1.2MPa; the lamination line speed is 15m / min. During the segmented gradient hot-pressing composite process, the relative humidity of the production environment is controlled at 45%; the interface temperature between the surface waterproof substrate and the water-blocking barrier film is maintained at 55℃, so that the pre-sealed coating can undergo a stable in-situ cross-linking reaction and avoid the formation of bubble defects at the interface. S4. Apply a modified waterproof adhesive layer to the side of the water-blocking membrane that is away from the sealing transition layer. The water-blocking barrier membrane is one of aluminum-plastic composite membrane, PVDC coated membrane, or EVOH barrier membrane; the modified waterproof self-adhesive is an acrylic hydrophobic modified pressure-sensitive adhesive with a dry film thickness of 30μm and hydrophobic nano-silica particles dispersed within the adhesive layer. S5. A release film is laminated onto the surface of the self-adhesive layer to produce a multi-layer waterproof self-adhesive roll material. The release film is a single-sided silicone-coated PET release film with a thickness of 44μm. It is placed on the outside of the modified waterproof self-adhesive layer to isolate and protect it, preventing self-adhesion and contamination during roll storage and die-cutting processes. The release film is removed when the label is applied. S6. Die-cut the roll material to obtain the label blank, then apply UV sealant to the die-cut surface of the label blank online, and seal the cross-section after UV curing to obtain a high-sealing multi-layer waterproof self-adhesive label. Among them, the UV sealant is a UV acrylic resin system containing hydrophobic monomers, the coating width covers the cut surface of the mold, the UV sealant coating thickness is 5μm, and the UV curing exposure dose is 900mJ / cm². The resulting high-sealing multilayer waterproof self-adhesive label comprises, from the outside to the inside: a surface waterproof substrate, a cross-linked sealing transition layer, a water-blocking barrier film, a modified waterproof self-adhesive layer, and a release film; the cross-linked sealing transition layer continuously fills the microscopic gaps between the surface waterproof substrate and the water-blocking barrier film.
[0031] Example 2: This application provides a high-sealing, multi-layer waterproof self-adhesive label manufacturing process, which includes the following steps: S1. Plasma activation pretreatment of the surface of the waterproof substrate; The surface waterproof substrate is any one of PET waterproof film, BOPP film or hydrophobic modified PE film. The plasma activation adopts normal pressure plasma treatment, with a treatment power of 80W, a treatment distance of 4mm and a treatment speed of 10m / min. S2. A cross-linked sealing prepolymer is continuously coated on one side of the activated surface waterproof substrate to form a pre-sealing coating. The crosslinked sealing prepolymer is a hydrophobically modified isocyanate-terminated polyurethane prepolymer, which is prepared from the following raw materials in parts by weight: 65 parts hydrophobic polycarbonate diol, 30 parts isophorone diisocyanate, 1 part long-chain alkyl hydrophobically modified monomer, 0.01 parts dibutyltin dilaurate, and 0.2 parts dehydrating agent. S3. The surface waterproof substrate with pre-sealed coating is combined with the water-blocking barrier membrane in a segmented gradient hot-pressing process, so that the pre-sealed coating undergoes an in-situ cross-linking reaction at the interface of the two substrates to generate a continuous sealing transition layer, thus obtaining a double-layer composite membrane. The method for preparing the cross-linked sealing prepolymer includes: vacuum dehydrating hydrophobic polycarbonate diol; sequentially adding isophorone diisocyanate and long-chain alkyl hydrophobic modified monomers under nitrogen protection, adding dibutyltin dilaurate and then carrying out an addition reaction at 75°C; cooling down after the free NCO content reaches 2.0%, adding a dehydrating agent and mixing, filtering and encapsulating to obtain the cross-linked sealing prepolymer; The coating dry film thickness is controlled at 2μm; the segmented gradient hot pressing is divided into two stages: the first stage is low-pressure exhaust, hot pressing temperature is 45℃, and roller pressing pressure is 0.2MPa; the second stage is high-pressure cross-linking and lamination, hot pressing temperature is 55℃, and roller pressing pressure is 0.8MPa; the lamination line speed is 5m / min. During the segmented gradient hot-pressing composite process, the relative humidity of the production environment is controlled at 30%; the interface temperature between the surface waterproof substrate and the water-blocking barrier film is maintained at 40℃, so that the pre-sealed coating can undergo a stable in-situ cross-linking reaction and avoid the formation of bubble defects at the interface. S4. Apply a modified waterproof adhesive layer to the side of the water-blocking membrane that is away from the sealing transition layer. The water-blocking barrier membrane is one of aluminum-plastic composite membrane, PVDC coated membrane, or EVOH barrier membrane; the modified waterproof self-adhesive is an acrylic hydrophobic modified pressure-sensitive adhesive with a dry film thickness of 15μm and hydrophobic nano-silica particles dispersed within the adhesive layer. S5. A release film is laminated onto the surface of the self-adhesive layer to produce a multi-layer waterproof self-adhesive roll material. The release film is a single-sided silicone-coated PET release film with a thickness of 38μm. It is placed on the outside of the modified waterproof adhesive layer to isolate and protect the adhesive layer, preventing self-adhesion and contamination during roll storage and die-cutting processes. The release film is removed when the label is applied. S6. Die-cut the roll material to obtain the label blank, then apply UV sealant to the die-cut surface of the label blank online, and seal the cross-section after UV curing to obtain a high-sealing multi-layer waterproof self-adhesive label. The UV sealant is a UV acrylic resin system containing hydrophobic monomers. The coating width covers the cut surface of the mold, the UV sealant coating thickness is 2μm, and the UV curing exposure dose is 600mJ / cm².
[0032] Example 3: This application provides a high-sealing, multi-layer waterproof self-adhesive label manufacturing process, which includes the following steps: S1. Plasma activation pretreatment of the surface of the waterproof substrate; The surface waterproof substrate is any one of PET waterproof film, BOPP film or hydrophobic modified PE film. The plasma activation adopts normal pressure plasma treatment, with a treatment power of 160W, a treatment distance of 10mm and a treatment speed of 30m / min. S2. A cross-linked sealing prepolymer is continuously coated on one side of the activated surface waterproof substrate to form a pre-sealing coating. The crosslinked sealing prepolymer is a hydrophobically modified isocyanate-terminated polyurethane prepolymer, which is prepared from the following raw materials in parts by weight: 85 parts hydrophobic polycarbonate diol, 10 parts isophorone diisocyanate, 5 parts long-chain alkyl hydrophobically modified monomer, 0.15 parts dibutyltin dilaurate, and 1 part dehydrating agent. S3. The surface waterproof substrate with pre-sealed coating is combined with the water-blocking barrier membrane in a segmented gradient hot-pressing process, so that the pre-sealed coating undergoes an in-situ cross-linking reaction at the interface of the two substrates to generate a continuous sealing transition layer, thus obtaining a double-layer composite membrane. The method for preparing the cross-linked sealing prepolymer includes: vacuum dehydrating hydrophobic polycarbonate diol; sequentially adding isophorone diisocyanate and long-chain alkyl hydrophobic modified monomers under nitrogen protection, adding dibutyltin dilaurate and then carrying out an addition reaction at 85°C; cooling down after the free NCO content reaches 3.2%, adding a dehydrating agent and mixing, filtering and encapsulating to obtain the cross-linked sealing prepolymer; The coating dry film thickness is controlled at 12μm; the segmented gradient hot pressing is divided into two stages: the first stage is low-pressure exhaust, hot pressing temperature is 55℃, and roller pressing pressure is 0.6MPa; the second stage is high-pressure cross-linking and lamination, hot pressing temperature is 75℃, and roller pressing pressure is 1.6MPa; the lamination line speed is 25m / min. During the segmented gradient hot pressing process, the relative humidity of the production environment is controlled at 60%; the interface temperature between the surface waterproof substrate and the water-blocking barrier film is maintained at 70℃, so that the pre-sealed coating can undergo a stable in-situ cross-linking reaction and avoid the formation of bubble defects at the interface. S4. Apply a modified waterproof adhesive layer to the side of the water-blocking membrane that is away from the sealing transition layer. Among them, the water-blocking barrier film is one of aluminum-plastic composite film, PVDC coated film or EVOH barrier film, and the modified waterproof self-adhesive is acrylate hydrophobic modified pressure-sensitive adhesive with a dry film thickness of 45μm and hydrophobic nano silica particles dispersed in the adhesive layer. S5. A release film is laminated onto the surface of the self-adhesive layer to produce a multi-layer waterproof self-adhesive roll material. The release film is a single-sided silicone-coated PET release film with a thickness of 50μm. The release film is placed on the outside of the modified waterproof self-adhesive layer to isolate and protect the self-adhesive layer and prevent the self-adhesive from self-adhesion and contamination during roll storage and die-cutting processes. When the label is used, the release film is peeled off. S6. Die-cut the roll material to obtain the label blank, then apply UV sealant to the die-cut surface of the label blank online, and seal the cross-section after UV curing to obtain a high-sealing multi-layer waterproof self-adhesive label. The UV sealant is a UV acrylic resin system containing hydrophobic monomers. The coating width covers the cut surface of the mold, the UV sealant coating thickness is 8μm, and the UV curing exposure dose is 1200mJ / cm².
[0033] Comparative Example 1: The only difference between this comparative example and Example 1 is that step S2 is omitted, the surface of the waterproof substrate is not coated with cross-linked sealing prepolymer, and it is directly composited with the EVOH water-blocking barrier membrane in a segmented gradient hot-pressing process; the other raw material components, proportions and preparation processes are the same as in Example 1.
[0034] Comparative Example 2: The only difference between this comparative example and Example 1 is that after the label blank is obtained by die-cutting the roll material, the S6UV sealant coating and UV curing section sealing process is omitted, and the cut surface of the label mold is kept exposed; the other raw material components, proportions and preparation processes are the same as in Example 1.
[0035] Comparative Example 3: The only difference between this comparative example and Example 1 is that in step S2, the hydrophobic modified isocyanate-terminated polyurethane crosslinking sealing prepolymer is replaced with ordinary non-crosslinked polyurethane dry composite adhesive, and the coating dry film thickness is also controlled to 7μm; the UV sealing process of section S6 is completely retained; the remaining raw material components, proportions and preparation processes are the same as in Example 1.
[0036] Comparative Example 4: The only difference between this comparative example and Example 1 is that it simulates the conventional multi-layer self-adhesive label manufacturing process on the market, while canceling the S2 pre-sealing coating process and the S6 die-cutting UV sealing process; the surface waterproof substrate is directly hot-pressed and laminated with the barrier film, and no sealing treatment is performed on the cut surface after die-cutting; the other raw material components, proportions and preparation processes are the same as in Example 1.
[0037] Experiment 1: Comparative Experiment on the Manufacturing Process Performance of a High-Sealing Multilayer Waterproof Self-Adhesive Label 1. Test sample Test samples: Multi-layer waterproof self-adhesive label samples prepared by Examples 1, 2, 3, Comparative Examples 1, 2, 3, and 4; all samples were uniformly cut to 100mm × 50mm.
[0038] 2. Sample pretreatment All samples were placed in an environment of 23℃ and 50% relative humidity for 24 hours to adjust their condition and set aside for later use; 304 stainless steel plate was selected as the bonding substrate, and the samples were flatly pasted on the substrate surface to eliminate air bubbles at the bonding interface.
[0039] 3. Testing items and methods 3.1 Interlayer peel strength test Test basis: GB / T2790-2021 "Test method for 180° peel strength of adhesives" Test method: The 180° peel test was carried out using a universal testing machine with a tensile speed of 300 mm / min. The peel strength between the surface waterproof substrate and the water-blocking barrier film was measured. Each group of samples was tested in parallel for 5 times. The maximum and minimum values were removed, and the arithmetic mean of the remaining test data was taken as the final result. The unit is N / 15mm.
[0040] 3.2 Durability test under continuous immersion at room temperature Test method: The stainless steel plate with the label attached was completely immersed in 25℃ deionized water and left to soak. The condition of the sample was continuously observed, and the time when the first interlayer bubbling, watermark penetration, and delamination occurred was recorded. This time was defined as the immersion failure time, in hours. Three parallel samples were tested in each group, and the time when the failure occurred first was taken as the immersion failure time of the group.
[0041] 3.3 Damp-heat accelerated aging and water seepage test Test conditions: temperature 60℃, relative humidity 90%, total aging time 500h. After aging, the samples were removed and allowed to cool to room temperature. The water seepage, blistering, and delamination at the label interface were visually observed and rated according to a pre-defined water seepage level standard: Level 0: No water seepage, no watermark, no blistering, no delamination at the interface; Level 1: Slight water seepage, only a fine watermark appears at the cut edge, no blistering, and the watermark does not spread inward; Level 2: Moderate water seepage, the watermark spreads inward along the interlayer interface, and small blisters appear locally; Level 3: Severe water seepage, large area of interlayer watermark, obvious blistering, accompanied by interlayer delamination. The experimental results are shown in Table 1.
[0042] Table 1: Example 1 6.8 ≥1200 0 Example 2 5.7 960 0 Example 3 6.1 1050 0 Comparative Example 1 4.2 520 1 Comparative Example 2 4.5 580 1 Comparative Example 3 3.3 360 2 Comparative Example 4 2.1 180 3 See attached document Figure 1 and attached Figure 2 Based on the various embodiments and comparative examples, it can be seen that: Examples 1-3, employing the complete process of this application, possess both interlayer cross-linking sealing and UV sealing structure at the cut surface, exhibit significantly superior waterproofing performance compared to all comparative examples. Comparative examples 1 and 2, retaining only a single sealing method, show a significant decrease in waterproofing effect, demonstrating the synergistic effect of the two-layer sealing structure; Comparative example 3, using ordinary composite adhesive instead of the dedicated prepolymer, experiences a substantial decrease in sealing performance, verifying the crucial role of the prepolymer material system; Comparative example 4, employing a traditional process without a sealing structure, exhibits the worst waterproofing performance. This confirms that the combined solution of interlayer cross-linking sealing and UV sealing at the cut surface, achieved through a specific prepolymer, effectively opens two seepage paths, resulting in a longer-lasting waterproofing effect than expected.
[0043] In summary, based on Examples 1-3 and Comparative Example 1, and in conjunction with Table 1, it can be seen that Examples 1-3 fully utilize the process of this application, relying on the cross-linked sealing prepolymer to form a continuous hydrophobic sealing transition layer at the substrate interface through in-situ cross-linking. Simultaneously, with the dual protection of UV sealing at the cut surface, it can seal two water seepage channels: the micro-gap at the membrane interface and the edge cut. The samples exhibit higher interlayer peel strength, longer immersion failure time, and a damp heat aging water seepage level of 0. In contrast, Comparative Example 1 removes the interlayer cross-linked sealing structure, retaining only the cross-sectional UV sealing. Water vapor can continuously penetrate inward from the micro-gap between the surface waterproof substrate and the water-blocking membrane, resulting in decreased interlayer bonding strength, significantly shortened immersion failure time, and a damp heat aging water seepage level of 1. This proves that the interlayer in-situ cross-linked sealing transition layer is the key structure to ensure the long-term waterproof performance of the label. Without this structure, a single cross-section seal alone cannot prevent water seepage at the interlayer interface. The cross-linked sealing prepolymer is hot-pressed in-situ cross-linked to build a dense and continuous hydrophobic interface, which effectively inhibits the diffusion and migration of water vapor between the film layers. This interlayer sealing structure and the UV sealing of the mold cut surface work together to produce a synergistic effect. Both are indispensable and work together to achieve excellent and long-lasting waterproof sealing effect.
[0044] Combining Examples 1-3 and Comparative Example 2 with Table 1, it can be seen that Comparative Example 2 retains the interlayer cross-linking sealing process but eliminates the UV sealing of the mold cut surface, leaving the label mold cut surface exposed. Moisture can penetrate through the cut surface via capillary action, resulting in decreased interlayer peel strength, significantly shortened immersion failure time, and a moisture aging water seepage level of 1. These results indicate that interlayer sealing alone cannot block the capillary water seepage channels at the mold cut surface; the UV-cured sealing layer at the mold cut surface can seal the label edge cut, preventing moisture from intruding laterally, and forming a synergistic waterproof system with the interlayer cross-linking sealing transition layer.
[0045] As can be seen from Examples 1-3 and Comparative Example 3, and Table 1, although Comparative Example 3 fully retains the interlayer coating process and the cross-sectional UV sealing process, it replaces the special cross-linked sealing prepolymer with ordinary non-cross-linked polyurethane composite adhesive. Ordinary adhesives cannot form a three-dimensional hydrophobic cross-linked network, easily absorbing water and swelling after immersion, resulting in decreased interface sealing, significantly reduced interlayer peel strength and immersion service life, and a damp heat aging seepage level of 2. This confirms that the cross-linked sealing prepolymer with the composition specified in this application is the core material basis for constructing a long-lasting interlayer waterproof interface.
[0046] Combining Examples 1-3 and Comparative Example 4 with Table 1, it can be seen that Comparative Example 4 simulates the traditional multilayer self-adhesive label manufacturing process. It lacks both an interlayer cross-linking sealing transition layer and a sealing measure at the cut surface. Moisture can rapidly penetrate from both the film layer gaps and the label cut, resulting in the lowest interlayer peel strength, the shortest immersion failure time, and a maximum hygrothermal aging water penetration level of 3. The comparative results clearly demonstrate that the traditional process relies solely on the film's own waterproofing ability, exhibiting significant shortcomings in waterproofing. This application, through a combination of in-situ interlayer cross-linking sealing and cross-sectional UV sealing, constructs a three-dimensional double waterproof barrier, achieving a significant technical improvement compared to existing conventional processes.
[0047] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A manufacturing process for high-sealing, multi-layer waterproof self-adhesive labels, characterized in that, Includes the following steps: S1. Plasma activation pretreatment of the surface of the waterproof substrate; S2. A cross-linked sealing prepolymer is continuously coated on one side of the activated surface waterproof substrate to form a pre-sealing coating. S3. The surface waterproof substrate with pre-sealed coating is combined with the water-blocking barrier membrane in a segmented gradient hot-pressing process, so that the pre-sealed coating undergoes an in-situ cross-linking reaction at the interface of the two substrates to generate a continuous sealing transition layer, thus obtaining a double-layer composite membrane. S4. Apply a modified waterproof adhesive layer to the side of the water-blocking membrane that is away from the sealing transition layer. S5. A release film is laminated onto the surface of the self-adhesive layer to produce a multi-layer waterproof self-adhesive roll material. S6. The roll material is die-cut to obtain the label blank. Then, UV sealant is applied online to the die-cut surface of the label blank. After UV curing, the cross-section is sealed to obtain a high-sealing multi-layer waterproof self-adhesive label.
2. The manufacturing process for a high-sealing, multi-layer waterproof self-adhesive label according to claim 1, characterized in that, In step S1, the surface waterproof substrate is any one of PET waterproof film, BOPP film or hydrophobic modified PE film. The plasma activation adopts atmospheric pressure plasma treatment, with a treatment power of 80-160W, a treatment distance of 4-10mm and a treatment speed of 10-30m / min.
3. The manufacturing process for a high-sealing, multi-layer waterproof self-adhesive label according to claim 1, characterized in that, In step S2, the crosslinked sealing prepolymer is a hydrophobically modified isocyanate-terminated polyurethane prepolymer, which is prepared by the following parts by weight of raw materials: 65-85 parts of hydrophobic polycarbonate diol, 10-30 parts of isophorone diisocyanate, 1-5 parts of long-chain alkyl hydrophobically modified monomer, 0.01-0.15 parts of dibutyltin dilaurate, and 0.2-1 parts of dehydrating agent.
4. The manufacturing process for a high-sealing, multi-layer waterproof self-adhesive label according to claim 1, characterized in that, In step S3, the method for preparing the crosslinked sealing prepolymer includes: vacuum dehydrating hydrophobic polycarbonate diol; sequentially adding isophorone diisocyanate and long-chain alkyl hydrophobic modified monomers under nitrogen protection, adding dibutyltin dilaurate and then carrying out an addition reaction at 75-85°C; cooling down after the free NCO content reaches 2.0%-3.2%, adding a dehydrating agent and mixing, filtering and encapsulating to obtain the crosslinked sealing prepolymer.
5. The manufacturing process for a high-sealing, multi-layer waterproof self-adhesive label according to claim 1, characterized in that, In step S3, the thickness of the coated dry film is controlled between 2 and 12 μm; the segmented gradient hot pressing is divided into two stages: the first stage is low-pressure exhaust, with a hot pressing temperature of 45 to 55°C and a roller pressing pressure of 0.2 to 0.6 MPa; the second stage is high-pressure cross-linking and lamination, with a hot pressing temperature of 55 to 75°C and a roller pressing pressure of 0.8 to 1.6 MPa; the lamination linear speed is 5 to 25 m / min.
6. The manufacturing process for a high-sealing, multi-layer waterproof self-adhesive label according to claim 1, characterized in that, During the segmented gradient hot-pressing composite process in step S3, the relative humidity of the production environment is controlled at 30% to 60%; the interface temperature between the surface waterproof substrate and the water-blocking barrier film is maintained at 40 to 70°C, so that the pre-sealed coating can undergo a stable in-situ cross-linking reaction and avoid the formation of bubble defects at the interface.
7. The manufacturing process for a high-sealing, multi-layer waterproof self-adhesive label according to claim 1, characterized in that, In step S4, the water-blocking barrier membrane is one of aluminum-plastic composite membrane, PVDC coated membrane or EVOH barrier membrane, and the modified waterproof self-adhesive is acrylate hydrophobic modified pressure-sensitive adhesive with a dry film thickness of 15-45 μm and hydrophobic nano silica particles dispersed in the adhesive layer.
8. The manufacturing process for a high-sealing, multi-layer waterproof self-adhesive label according to claim 1, characterized in that, In step S5, the release film is a single-sided silicone-coated PET release film with a thickness of 38-50 μm. The release film is placed on the outside of the modified waterproof self-adhesive layer to isolate and protect the self-adhesive layer and prevent the self-adhesive from self-adhesion and contamination during roll storage and die-cutting processes. When the label is pasted and used, the release film is peeled off.
9. The manufacturing process for a high-sealing, multi-layer waterproof self-adhesive label according to claim 1, characterized in that, In step S6, the UV sealant is a UV acrylic resin system containing hydrophobic monomers, the coating width covers the cut surface of the mold, the UV sealant coating thickness is 2-8 μm, and the UV curing exposure dose is 600-1200 mJ / cm².
10. The manufacturing process for a high-sealing, multi-layer waterproof self-adhesive label according to claim 1, characterized in that, The resulting high-sealing multilayer waterproof self-adhesive label comprises, from the outside to the inside: a surface waterproof substrate, a cross-linked sealing transition layer, a water-blocking barrier film, a modified waterproof self-adhesive layer, and a release film; the cross-linked sealing transition layer continuously fills the microscopic gaps between the surface waterproof substrate and the water-blocking barrier film.